Diagnostic Accuracy of Air Puff Versus Goldmann Applanation Tonometer (Gold Standard) in Measuring Intraocular Pressure Abnormality in Primary Open Angle Glaucoma - Chakar Tajwidi, Saifullah Khan Tareen, Muhammad Amin, Iftikhar-Ul-Haq Tareen, Muhammad Afzal Khan, Shoaib Ahmed Kashani (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Glaucoma is a major cause of blindness worldwide. Intraocular pressure (IOP) disrupts axoplasmic transport in the optic nerve fibers due to compression, leading to the death of retinal ganglion cells. The Goldmann applanation tonometer (GAT) is widely regarded as the gold standard for measuring IOP. The air-puff tonometer also operates on the principle of applanation but uses a puff of air to flatten the central cornea and estimate IOP. Objective: To assess the diagnostic accuracy of the of air puff vs Goldmann applanation tonometer (gold standard) in measuring intraocular pressure abnormality in primary open angle glaucoma. Methodology: This cross-sectional comparative study was carried out at Teaching Hospital, Mekran Medical College, Turbat Kech from 1st March 2023 to 31st August 2023 and 200 patients were included. The patients were divided into two groups and each group had 100 patients. Group 1 had patients whose intraocular pressure (IOP) was assessed using the c while in group 2 IOP was measured using the air puff tonometer. In cases of Goldmann applanation tonometer topical anesthesia was achieved using 0.5% drops, and fluorescein dye was applied using a strip placed in the conjunctival sac. The examiner observed the semicircular mires to determine the force required for applanation, which was used to estimate IOP. In contrast, the air puff tonometer uses a short burst of air to briefly flatten the cornea. The device calculates IOP based on the corneal deformation response to this air pulse. Results: There were majority of the females than males with a mean age of 53.11±11.95 years. The group 1 and group 2 belonged to age groups 18-72 and 19-75 years respectively. The Mean ± SD intraocular pressure in group 1 of the Goldmann applanation tonometer was 13.84±2.29 mmHg while the IOP of the group 2 air puff tonometer was 17.43±2. 30mmHg using Goldmann tonometry, 8% (2 patients) had intraocular pressure (IOP) readings between 7–10 mmHg, 28% (n=7) between 11–14 mmHg. In comparison, air puff tonometry showed that 4% (n=4) had IOP readings of 7–10 mmHg, and 52% (n=52) between 15–18 mmHg in comparison with 35% (n=35%) in Group 1 (GAT having 15-18 mmHg IOP). Conclusion: The comparison within air puff vs Goldmann applanation tonometer (gold standard) in measuring intraocular pressure abnormality in primary open angle glaucoma presented high diagnostic accuracy of Air puff tonometry with significant efficient and elevated intraocular pressure. Keywords: Accuracy, Air puff, Goldmann applanation tonometer, Intraocular pressure abnormality, Primary open angle glaucoma